Assessment of the Effects of Pediatric Attention Deficit Hyperactivity Disorder on Family Stress and Well-Being: Development of the IMPACT 1.0 Scale. (March 2019) - Bauer, Nerissa S.; Ofner, Susan; Moore, Courtney; Lynch, Dustin; Wiehe, Sarah E.; Downs, Stephen M.; Carroll, Aaron E.; Kronenberger, William G.
Medications may lessen core symptoms of attention deficit hyperactivity disorder (ADHD), yet families continue to report stress and have a low quality of life. Primary care providers manage almost half of all children with ADHD but do not have a brief measure to assess ADHD impacts on family in the context of everyday family life. The IMPACT (Impact Measure of Parenting-Related ADHD Challenges and Treatment) 1.0 Scale was codeveloped with input from parent advisors and administered to 79 parents of children with ADHD. Exploratory factor analysis, correlations with validated instruments, and test-retest reliability were examined. Exploratory factor analysis resulted in 4 subscales (Misbehavior, Siblings, Time, School), which demonstrated moderate to high test-retest reliability. Scale domains were related to severity and change in ADHD symptoms. Significant correlations were found between IMPACT scores, adaptive functioning in the home, and ADHD-related quality of life. The IMPACT 1.0 Scale provides a novel, reliable, and valid method to assess family impact of ADHD.